2020
DOI: 10.1080/0284186x.2020.1731924
|View full text |Cite
|
Sign up to set email alerts
|

CD30 expression and survival in posttransplant lymphoproliferative disorders

Abstract: Background: Post-transplant lymphoproliferative disorder (PTLD) is a rare but life-threatening complication of transplantation. For refractory and relapsed PTLD new therapies are needed, such as the antibody-drug conjugate brentuximab vedotin that targets CD30. There is limited knowledge of CD30 expression in various subtypes of PTLD and its correlation to clinicopathological features. Therefore, we studied the expression of CD30 in PTLD following solid organ transplantation and correlated CD30 expression to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Finally, the role of CD30 in this case is interesting. Although CD30 expression varies in PTLD and is not associated with any specific type, 39 in murine models of influenza vaccination, it has been found that although CD30 is dispensable for the immune response, it plays a role in the persistence of T cells over time. 40 In fact, in monomorphic PTLD of B-cell type, CD30 has been found to be expressed in up to 79% of cases, compared with 38% of CD30 + cases in de novo diffuse large B-cell lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the role of CD30 in this case is interesting. Although CD30 expression varies in PTLD and is not associated with any specific type, 39 in murine models of influenza vaccination, it has been found that although CD30 is dispensable for the immune response, it plays a role in the persistence of T cells over time. 40 In fact, in monomorphic PTLD of B-cell type, CD30 has been found to be expressed in up to 79% of cases, compared with 38% of CD30 + cases in de novo diffuse large B-cell lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…Another CD30-expressing tumor type is post-transplant lymphoproliferative disorder, which is a rare complication of transplantation [104]. Up to 70% of these can be CD30-positive, suggesting a potential role for brentuximab vedotin in the treatment of this disorder [104]. Some CD30-positive B-cell specific lymphomas may also respond to brentuximab vedotin therapy.…”
Section: Targeting Cd30 In Other Lymphomasmentioning
confidence: 99%
“…In a phase II trial of brentuximab vedotin in patients with relapsed/refractory EBV-positive CD30-positive mature T, NK, or B-cell lymphoma, ORR was 48%, and at a median of 20 months follow-up, median PFS and OS were 6.2 months and 15.7 months, respectively [ 103 ]. Another CD30-expressing tumor type is post-transplant lymphoproliferative disorder, which is a rare complication of transplantation [ 104 ]. Up to 70% of these can be CD30-positive, suggesting a potential role for brentuximab vedotin in the treatment of this disorder [ 104 ].…”
Section: Targeting Cd30 In Other Lymphomasmentioning
confidence: 99%
“…The anti-CD30 antibody drug conjugate brentuximab vedotin (BV) is currently approved in combination with doxorubicin-based chemotherapy (BV-CHP) as a front-line therapy for CD30+ peripheral T-cell lymphomas (PTCL), after the completion of the phase III pivotal ECHELON-2 trial, where BV-CHP was found to be superior to CHOP. BV is now being investigated in the setting of PTLD, given that there is increasing evidence showing that the CD30+ antigen expression is frequently detected in PTLD [ 108 , 109 , 110 ]. ECHELON-2 excluded immunocompromised patients, given their poor survival outcomes.…”
Section: Treatmentmentioning
confidence: 99%